Prevalence of Gastroesophageal Reflux Disease among Diabetic Patients at Sharif Medical City Hospital, Lahore, Pakistan - Mehdi, Syed Muslim; Baig, Usman; Iqbal, Muhammad Shahid (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Diabetes mellitus has been linked to various gastrointestinal motility disorders, including gastroesophageal reflux disease (GERD).This study aimed to determine the proportion of GERD in patients with diabetes mellitus.Method: This descriptive cross-sectional study was conducted at the medical outpatient department of Sharif Medical City Hospital, Lahore, from October to December, 2020. Patients previously diagnosed with type II diabetes were included using non-probability consecutive sampling, and the GERDQ questionnaire was used to determine the frequency. IBM SPSS statistics version 23 was used for the analysis of data.Results: Of the 273 participants, 183 (67.0%) were male and the mean age was 51.13±12.8 years. The mean duration of diabetes was 6.97±4.76 years and oral hypoglycemic agents were used by 133 (48.7%) participants. Overall, 133 (48.7%) of the participants had GERD with a mean GERDQ score of 10.8(±1.4).Conclusion: Almost half (48.7%) of the participants have GERD; the most common symptom is regurgitation of stomach contents. Awareness should be raised, and early screening should be done to prevent long-term complications.